T cells in the microenvironment of solid pediatric tumors: the case of neuroblastoma - Maggi, Enrico; Landolina, Nadine; Munari, Enrico; Mariotti, Francesca Romana; Tumino, Nicola; Vacca, Paola; Azzarone, Bruno; Moretta, Lorenzo (Frontiers in Immunology, 2025)
Neuroblastoma (NB) is an immunologically “cold” tumor with poor or no inflamed substrates as most of solid pediatric tumors (SPT). Consistent data indicate that NB tumor microenvironment (TME) is dominated by myeloid cells, with little (but variable) T cell infiltration. The obstacles to lymphocyte infiltration and to their anti-tumor activity are due to different tumor immune evasion strategies, including loss of HLA Class I molecules, high expression of immune checkpoint molecular ligands leading to exhaustion of T effector (and NK) cells, induction of T regulatory, myeloid and stromal cells and secretion of immunosuppressive mediators. In odds with adult solid tumors, NB displays weak immunogenicity caused by intrinsic low mutational burden and scant expression of neoepitopes in the context of MHC-class I antigens which, in turn, are particularly poorly expressed on NB cells, thus inducing low anti-tumor T cell responses. In addition, NB is generated from embryonal cells and is the result of transcriptional abnormalities and not of the accumulation of genetic mutations over time, thus further explaining the low immunogenicity. The poor expression of immunogenic molecules on tumor cells is associated with the high production of immunosuppressive factors which further downregulate lymphocyte infiltration and activity, thus explaining the limited efficacy of new drugs in NB, as immune checkpoint inhibitors. This review is focused on examining the role of T effector and regulatory cells infiltrating TME of NB, taking into account their repertoire, phenotype, function, plasticity and, importantly, predictive value for defining novel targets for therapy.